Deoxygenative silylation of aromatic carbonyl compounds with HSiCl3 in the presence of quaternary phosphonium chloride: A facile route to arylmethyltrichlorosilane - Han, Joon Soo; Kang, Seung-Hyun; Jung, Ii Nam; Yoo, Bok Ryul (ELSEVIER SCIENCE INC, 2016)
Aromatic carbonyl compounds such as aromatic aldehydes and ketones [(RRC)-R-1-C-2=O: R-1=H; R-2=Ph (1a), 2,4-Cl2Ph (1b), 2,4-Me2Ph (1c): R-1=Ph; R-2=Ph (1d), 4-C1Ph (1e), 4-MePh (2f), 2,4-Me2Ph (1g) undergo the deoxygenative silylation with HSiCl3 in the presence of Bu4PCl at 150 degrees C within 1.0-1.5 h to give arylmethyltrichlorosilanes 2 ((RRCH)-R-1-C-2-SiCl3) in high yields (85-95%). The reactivity of aromatic carbonyl compounds decreases with increasing the electron withdrawing ability of substituent(s) on the benzene ring. A highly efficient synthetic route to arylmethyltrichlorosilanes has been developed starting from aromatic aldehydes and ketones in this study. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: C COUPLING REACTION; ORGANOSILICON COMPOUNDS; PENTACOORDINATE HYDRIDOSILICATES; SELECTIVE REDUCTION; TRICHLOROSILANE; HYDROSILANES; REACTIVITY; KETONES; HYDROSILYLATION; DIHYDRIDOSILICATES